The efficacy of Climate Change on Sustainability of Supply Chain Management - Gajendra Singh (Penerbit Jurnal Indonesia, 2023)
Natural hazards are the sudden catastrophic events which destructs the economy (Alcántara- Ayala, 2002) and the consequences of the same affects human system, natural environment and built environment (Beekharry, 2015). Climate change is the common disastrous event affecting human societies (Stern Review, 2006). As the change in climate directly affects supply chain management of products (Dasaklis and Pappis, 2013) and the market demand also fluctuates as well due to price competitive environment (Jena and Jog, 2016). Consequently, focus of this research is to analyze the impact of natural disasters on variables mainly supply chain management, precautions taken during disasters, Tourism Industry and market demand of goods and services. By employing exploratory research design with various statistical tools, it comes up with remarkable results and concludes that Supply chain management is considered as critical one as it is more vulnerable towards disasters and gets inefficient resulting into disruptive supply chain networks.